Large Banks, Market-based Banking, and the Financialisation of Danish Mortgage Markets. Issue 1 (2nd January 2022) - Gallagher, Patrick
ABSTRACT: This paper puts forward three arguments; firstly, the origions of Danish market-based banking can be traced to the shift by a small group of large commercial banks into the mortgage lending business. Secondly, the Danish case demonstrates the centrality of housing and the politics of mortgage market liberalisation to the rise of market-based banking. And finally, that national diversity in the form of market-based banking mattered for Danish financial stability. Historically, the Danish mortgage model was characterised by cooperative mortgage associations focused on the provision of stable equitable access to housing finance. However, as we shall see, the 1986 financial crisis marked a turning point for Danish finance, and from that point on, a small group of the large commercial bank became increasingly influential. The empirical sections outline three stages to the transformation of Danish finance. In the 1980s, a financial crisis led to the creation of a new type of large commercial bank. In the 1990s, the large banks diversified into the mortgage business crowding out the traditional mortgage banks. Finally, in the 2000s, the large banks provide credit for a massive housing bubble through new forms of market-based banking.